STUDY OF CLINICAL AND MORPHOLOGICAL CHANGES IN ORGANS AND TISSUES OF THE ORAL CAVITY IN ADULT WOMEN AND THEIR ANALYSIS - Toshpulatova Kamola Ulugbek kizi; Islаmova Nilufar Bustanovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation. During menopause, irreversible changes in the hormonal function of the ovaries occur, the concentration of estrogens decreases. It is during this period that a progressive increase in various diseases is noted. The study of the dental status in menopausal women has proven the existence of a relationship between a decrease in estrogen concentration and a sharp increase in dental diseases. Because the oral mucosa and salivary glands contain estrogen receptors, changes in hormonal levels can be seen directly in the mouth. Leimola-Virtanen et al confirmed the presence of estrogen mRNA and immunoreactive protein in the oral mucosa and salivary glands, which also confirms its biological role. Thus, the climacteric period is characterized by a disorder of metabolism and function in the tissues of the oral cavity. As a result, tooth loss, periodontal disease, increased bone resorption of the alveolar processes are observed.